ANATOMICAL DISSECTION AND CT IMAGING OF THE ANTERIOR CRUCIATE AND MEDIAL COLLATERAL LIGAMENT FOOTPRINT ANATOMY IN SKELETALLY IMMATURE CADAVER KNEES. Issue 3 (31st March 2019) - Shea, Kevin; Cannamela, Peter C.; Dingel, Aleksei; Fabricant, Peter D.; Polousky, John D.; Anderson, Allen; Ganley, Theodore J.
Background: Anterior cruciate ligament (ACL) and medial collateral ligament (MCL) injuries in skeletally immature patients are increasingly recognized and surgically treated. However, the relationship between the footprint anatomy and the physes are not clearly defined. The purpose of this study was to identify the origin and insertion of the ACL and MCL, and define the footprint anatomy in relation to the physes in skeletally immature knees. Methods: Twenty-nine skeletally immature knees from 16 human cadaver specimens were dissected and divided into two groups: Group A (ages 2-5 years), and Group B (ages 7-11 years). Metallic markers were placed to mark the femoral and tibial attachments of the ACL and MCL. CT scans were obtained for each specimen used to measure the distance from the center of the ligament footprints to the respective distal femoral and proximal tibial physes. Results: Median distance from the ACL femoral epiphyseal origin to the distal femoral physis was 0.30 cm (interquartile range, 0.20 cm to 0.50 cm) and 0.70 cm (interquartile range, 0.45 cm to 0.90 cm) for Groups A and B, respectively. The median distance from the ACL epiphyseal tibial insertion to the proximal tibial physis for Groups A and B were 1.50 cm (interquartile range, 1.40 cm to 1.60 cm) and 1.80 cm (interquartile range, 1.60 cm to 1.85 cm), respectively. Median distance from the MCL femoral origin on the epiphysis to the distal femoral physis was 1.20 cm (interquartile range, 1.00 cm to 1.20 cm) and 0.85 cm (interquartile range, 0.63 cm to 1.00 cm) for Groups A and B, respectively. Median distance from the MCL insertion on the tibial metaphysis to the tibial physis was 3.05 cm (interquartile range, 2.63 cm to 3.30 cm) and 4.80 cm (interquartile range, 3.90 cm to 5.10 cm) for Groups A and B, respectively. Conclusion: Surgical reconstruction is a common treatment for ACL injury, and occasionally MCL reconstruction or repair is also required. Cadaveric dissection and CT scanning of exceptionally rare pediatric tissue clearly defines the location of the ACL and MCL with respect to the femoral and tibial physes, and may guide surgeons for physeal respecting procedures for both ACL reconstruction, and ACL repair procedures. Clinical Relevance: In addition to ACL reconstruction, recent basic science and clinical research suggest that ACL repair may be more commonly performed in the future. MCL repair and reconstruction is also occasionally required in skeletally immature patients. This information may be useful to help surgeons avoid or minimize physeal injury during ACL/MCL reconstructions and/or repair in skeletally immature patients. Figure 1. Disarticulated 9-year-old, male, left knee. Metallic push pins mark the proximal and distal extent of the ACL femoral origin (A, white line) and the proximal, distal, medial, and lateral extents of the tibial insertion (B, black box). Figure 2. 11-year-old male left knee. Metallic push pins mark the midpoint of the MCL femoral origin (A) and tibial insertion (B). Note the reflected pes anserine structure of the sartorious, gracilis, and semitendinosis tendons just anterior to the distal extent of the MCL on the tibia. The 2 silver/grey pins on the tibial highlight the sartorius (most proximal location on anterior tibia crest), gracilis (central location), and sartorious (most distal location) Figure 3. Relationship of ACL (black squares) and MCL origin (white diamonds) midpoints to the distal femoral physis. Figure 4. Relationship of ACL (black squares) and MCL (white diamonds) midpoint insertions to the proximal tibial physis.